Biodegradable JDBM coating stent has potential to be used in the treatment of benign biliary strictures. (17th February 2021) - Guo, Lili; Yu, Lanting; Zhao, Qiuyan; Gong, Xiaoyuan; Xie, Haoran; Yuan, Guangyin; Li, Baiwen; Wan, Xinjian
Abstract: In our previous study, to find out the optimal alloy suitable for biliary surgery, magnesium alloy Jiao Da Bio-magnesium (denoted as JDBM) alloy, Zn–3Cu alloys, and their respective coating (MgF2 –PDLLA) products were produced for our research. We found that JDBM seems to be a potential material for clinical biliary stent application due to its uniform degradation and good compatibility. In order to apply the JDBM alloy to treat benign bile duct stricture, our group prepared the bare JDBM and its coating product into finished stents by mesh weaving carving technology and conducted the mechanical property tests, degradation tests and biocompatibility tests. During the mechanical property tests, we found the bare JDBM stent was more suitable than titanium alloy stent when applies to the bile duct, and the coating of the JDBM coating stent has no effect on its mechanical properties. Our in vitro and in vivo experiments revealed that the degradation rate of the JDBM coating stent is lower than that of the JDBM stent, and both stents were biosafe. Thus, there is promise for JDBM coating stents for the treatment of benign biliary strictures.